2022
DOI: 10.1002/cb.2109
|View full text |Cite
|
Sign up to set email alerts
|

Perceived deception and online repurchase intention: The moderating effect of product type and consumer regulatory orientation

Abstract: Limited by e-tailers' ability to present accurate information about their products, consumers often misunderstand and misinterpret product messaging, which can heighten their perception of deception among e-tailers and result in unfavorable consumer behaviors and actions. Integrating perceived deception and existing consumer behavior theories, this research examines the intricate relationships between product type (hedonic vs. utilitarian), consumer regulatory orientation (promotion vs. prevention), and their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 114 publications
0
3
0
Order By: Relevance
“…The sentiment of the review (positive or negative) can lead to opposite effects on prospective consumers (Hao et al, 2010). Earlier studies confirm that linguistic styles with language subjectivity boost consumers' purchase intentions (Liu et al, 2018;Nikbin et al, 2022;Wang et al, 2022). Studies also report significant differences in the micro-linguistic constituents of fake and genuine reviews (Chatterjee et al, 2021).…”
Section: Proposed Research Model and Hypotheses Developmentmentioning
confidence: 88%
“…The sentiment of the review (positive or negative) can lead to opposite effects on prospective consumers (Hao et al, 2010). Earlier studies confirm that linguistic styles with language subjectivity boost consumers' purchase intentions (Liu et al, 2018;Nikbin et al, 2022;Wang et al, 2022). Studies also report significant differences in the micro-linguistic constituents of fake and genuine reviews (Chatterjee et al, 2021).…”
Section: Proposed Research Model and Hypotheses Developmentmentioning
confidence: 88%
“…Chai et al (2019) found that lack of perceived benefits is a critical factor that negatively affects the adoption of mobile payment services among users in Malaysia. Similarly, Wang et al (2020) and Bashir and Madhavaiah (2021) revealed that perceived usefulness is a significant factor that positively affects the intention to use digital wallets in China.…”
Section: Lack Of Perceived Benefitmentioning
confidence: 94%
“…Specifically, in terms of action experience, a series of special interactive experiences such as fan interaction, game interaction and city-city interaction of blind box merchants enable consumers to participate in and integrate into the interactive situation, arousing the resonance of merchants and consumers, thus constantly stimulating consumers to buy repeatedly. In terms of related experience, consumers 'interactive sharing under a large number of high-heat blind box related topics meets their social needs, thus stimulating consumers' willingness to continue buying [12] . Accordingly, the following assumptions are made:…”
Section: The Relationship Between Marketing Stimulation and Consumers...mentioning
confidence: 99%